Phytochemical Screening of Ethyl Acetate Extract of Beta-beta Leaves (Lunasia amara Blanco) as Anticancer and Antimicrobial Based on Prediction of Activity Spectra for Substances (PASS) Online - Adriani, Adriani (Universitas Negeri Gorontalo, 2024)
Introduction: Beta-beta leaves (Lunasia amara Blanco) have anticancer and antibacterial activity, but the secondary metabolites involved are still not clearly known. The aim of this research is to screen secondary metabolites from beta-beta leaves that have potential anticancer and antibacterial properties using the Passonline server and determine potential compound target proteins using the Superpred online server.Method: Extraction of beta-beta leaves was carried out using the maceration method using ethyl acetate and identification of secondary metabolites using Liquid Chromatography High-Resolution Mass Spectrometry (LC HRMS). Prediction of the anticancer, antibacterial and toxicity potential of secondary metabolites of beta-beta leaves using Prediction of Activity Spectra for Substances (PASS) Online. Analysis of similarity to drugs using Lipinski rule of five and prediction of target proteins using the online superpred server.Results: There are 10 secondary metabolites each which have anticancer and antibacterial bioactivity. The compounds methyl cinnamate and 3,5-pyridinedicarboxylic acid are similar to drugs based on Lipisnki rule of five analysis and are non-toxic based on online PASS analysis. There are 3 target proteins for methyl cinnamate which are involved in anticancer and antibacterial activity, namely NFκβ P105, ADAM10 and Catephsin D.Conclusion: Ethyl acetate extract from beta-beta leaves contains secondary metabolites as anticancer and antibacterial based on Passonline server analysis. Methyl cinnamate is a potential secondary metabolite candidate as an anticancer and antibacterial with 3 target proteins, namely NFκβ P105, ADAM10 and Catephsin D. Key words: Anticancer, antibacterial, beta-beta, Lunasia amara, passonline, prediction